Celia Deane-Drummond, A Primer in Ecotheology: Theology for a Fragile Earth. (22nd February 2019) - Doran, Chris
Abstract : Celia Deane-Drummond, A Primer in Ecotheology: Theology for a Fragile Earth (Eugene, OR: Cascade Books, 2017), 167 pp., $23.00 (pbk), ISBN: 978-1-4982-3699-7.